Change research : a case study on collaborative methods for social workers and advocates - Shdaimah, Corey S. (Columbia University Press, 2011)
Collaborating with community members adds a critical dimension to social work research, providing practitioners with intimate knowledge of a community's goals and needs. Yet such partnerships needn't be one-sided. Answering the concerns of critics who doubt the benefits of community surveillance, intentional change research offers a reciprocal model of involvement, in which community advocates gain vital skills for dramatic social change. Sharing the inspiring story of one such partnernship, Corey Shdaimah, Roland Stahl, and Sanford Schram recount their work with community members.